2015
DOI: 10.1021/jm501799k
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of Pyrrolyl Diketo Acid Derivatives as Dual Inhibitors of HIV-1 Integrase and Reverse Transcriptase Ribonuclease H Domain

Abstract: The development of HIV-1 dual inhibitors is a highly innovative approach aimed at reducing drug toxic side effects as well as therapeutic costs. HIV-1 integrase (IN) and reverse transcriptase-associated ribonuclease H (RNase H) are both selective targets for HIV-1 chemotherapy, and the identification of dual IN/RNase H inhibitors is an attractive strategy for new drug development. We newly synthesized pyrrolyl derivatives that exhibited good potency against IN and a moderate inhibition of the RNase H function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…[5] Whereas no RNase Hinhibitor has reached clinicaltrials, alimited number of compounds have been reported, and they can be classifiedi nto two classes:m etal-chelating active-site inhibitors, which bind andc oordinate the two Mg 2 + ion cofactors, and allosteric inhibitors, which induce ac onformational change in the active site that disables the RNA:DNA hybrid substrate binding. [6][7][8][9][10] Allosteric inhibitors could be attractive both to counteract the development of resistants trains and to avoid the inhibition of relatedh ost enzymes, such as the humanR Nase H1. [11] Despite the significant progress achieved with combination antiretroviral therapy in the fight against human immunodeficiency virus (HIV) infection, the difficulty to eradicate the virus together with the rapid emergenceo fm ultidrug-resistant strains clearly underline ap ressing need for innovative agents, possibly endowed with novel mechanismso fa ction.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Whereas no RNase Hinhibitor has reached clinicaltrials, alimited number of compounds have been reported, and they can be classifiedi nto two classes:m etal-chelating active-site inhibitors, which bind andc oordinate the two Mg 2 + ion cofactors, and allosteric inhibitors, which induce ac onformational change in the active site that disables the RNA:DNA hybrid substrate binding. [6][7][8][9][10] Allosteric inhibitors could be attractive both to counteract the development of resistants trains and to avoid the inhibition of relatedh ost enzymes, such as the humanR Nase H1. [11] Despite the significant progress achieved with combination antiretroviral therapy in the fight against human immunodeficiency virus (HIV) infection, the difficulty to eradicate the virus together with the rapid emergenceo fm ultidrug-resistant strains clearly underline ap ressing need for innovative agents, possibly endowed with novel mechanismso fa ction.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrrolyl DKA derivatives were further explored to optimize dual inhibitors against IN and RNase H [ 141 ]. Two classes of pyrrolyl DKA derivatives were reported: the diketobutanoic and the diketohexenoic derivatives.…”
Section: Inis Approved For Clinical Applicationmentioning
confidence: 99%
“…All these findings confirm our initial hypothesis of multiple target binding. Unlike the known molecules capable of dual IN/RNase H inhibition or dual RDDP/RNase H inhibition, kuwanon‐L represents the first compound able to inhibit both the activity associated with HIV‐1 IN and the two activities associated with HIV‐1 RT. This new approach can be considered a solid starting point that demonstrates that the multiple‐target‐binding strategy can be successfully applied against HIV‐1.…”
Section: Figurementioning
confidence: 99%